Industry and occupational employment projections overview and highlights, 2024-34. - Rieley, Michael J. (Monthly Labor Review, 2026)
The article provides an overview of the U.S. Bureau of Labor Statistics (BLS) industry and occupational employment projections for 2024–2034, forecasting a total employment growth of 3.1 percent, or 5.2 million new jobs. The fastest-growing sectors are healthcare and social assistance (8.4 percent growth) and professional, scientific, and technical services (7.5 percent growth), driven largely by demographic trends such as an aging population and rising chronic health conditions. The information sector, particularly IT-related industries, is also projected to grow rapidly due to strong demand for software, cybersecurity, cloud computing, and artificial intelligence (AI) technologies, which will boost employment in computer and mathematical occupations. Conversely, retail trade is expected to decline, mainly due to e-commerce growth and the rise of electric vehicles reducing demand in gasoline stations, while transportation and warehousing will grow to support logistics and delivery needs. The article discusses the impact of AI, noting that while it may reduce employment demand in some occupations (e.g., sales, administrative support, arts and design), it will increase demand for computer-related occupations involved in AI development and implementation.